Circulating tumor cells are associated with poor overall survival in patients with cholangiocarcinoma. Issue 1 (7th August 2015) - Yang, Ju Dong; Campion, Michael B.; Liu, Minetta C.; Chaiteerakij, Roongruedee; Giama, Nasra H.; Ahmed Mohammed, Hager; Zhang, Xiaodan; Hu, Chunling; Campion, Victoria L.; Jen, Jin; Venkatesh, Sudhakar K.; Halling, Kevin C.; et al.
Abstract : Circulating tumor cells (CTCs) in blood are associated with poor survival of patients with breast, prostate, or colon cancer. We hypothesized that CTCs are associated with poor survival of patients with cholangiocarcinoma (CCA). Eighty‐eight patients with CCA were prospectively enrolled at Mayo Clinic Rochester between June 2010 and September 2014. The CellSearch system by Veridex was used for detection of CTCs in peripheral blood. Associations between CTC, patient and tumor characteristics, and survival were examined using the Cox's proportional hazards model. Fifteen patients (17%) were positive for CTC ≥2 and 8 patients (9%) for CTC ≥5. CTCs were associated with tumor extent. CTC ≥2 (hazard ratio [HR]: 2.5; 95% confidence interval [CI]: 1.1‐5.4; P = 0.02) and CTC ≥5 (HR, 4.1; 95% CI: 1.4‐10.8; P = 0.01) were both independent predictors of survival. In subgroup analyses, CTC ≥2 (HR, 8.2; 95% CI: 1.8‐57.5; P < 0.01) and CTC ≥5 (HR, 7.7; 95% CI: 1.4‐42.9; P = 0.02) were both associated with shorter survival among patients with metastasis. There was a trend toward association of CTC ≥5 with shorter survival in patients with nonmetastatic CCA (HR, 4.3; 95% CI: 1.0‐13.8; P = 0.06). CTC ≥2 (HR, 10.5; 95% CI: 2.2‐40.1; P < 0.01) and CTC ≥5 (HR, 10.2; 95% CI: 1.5‐42.3; P = 0.02) were both associated with shorter survival among patients with perihilar/distal CCA. CTC ≥5 was associated with shorter survival of patients with intrahepatic CCA (HR, 4.2; 95% CI: 1.1‐14.1; P = 0.04). Conclusion : CTCs were associated with more‐aggressive tumor characteristics and independently associated with survival in patients with CCA. Assessment of CTCs may be useful for identifying CCA patients at risk of early mortality. (Hepatology 2016;63:148–158)